The Evaluation of a monovalent Botulinum type F vaccine by Enzyme-Linked Immunosorbent Assay - Montgomery, Vicky A. (My University, 1996)
Clostridium botulinum produces 7 protein neurotoxins (A-G) for which the current vaccine protects against serotypes A-E. A recently developed, formalin-inactivated, pure botulinum type F toxoid was tested in 35 adult volunteers. The serum from the vaccinated volunteers was evaluated for antibody response, by ELISA, at various time intervals over the period of one year. Nonimmune serum from 150 individuals was tested to quantitate the baseline antibody response. The antibody response was measured for varying doses of vaccine (2, 5, or 10 jig), and after single or multiple (2 or 3 doses @ 10 pg) immunizations. Ten out of 15 (67%) individuals seroconverted after receiving a single dose. Six months after immunization, 20% were antibody-positive. After 2 immunizations, there was an 85% (17/20) seroconversion rate; 3 doses gave 90% (9/10) seroconversion. One year after initial immunization, 63% and 80% of individuals receiving two or three immunizations respectively, were antibody positive. After the third immunization, ELISA titers were positively correlated with mouse lethality neutralization titers (r² = 0.86). Paired sera from pre and post-immunization collections were tested for antibody cross-reactivity/booster-response to botulinum toxins A, B, C, and E after receiving the type F vaccine. Of five individuals, immunized first with the type F vaccine, three volunteers had a demonstrable enhancement in antibody response to type F toxin after receiving the pentavalent vaccine. Among 12 individuals immunized first with the pentavalent botulinum toxoid, one volunteer had an increased antibody response to type E toxin. The data suggest that the type F and pentavalent vaccines produce a cross-anamnestic response in some individuals. When given multiple immunizations, the botulinum type F vaccine elicits a protective antibody response. Single immunizations, at any of the tested dosages, elicited a lower and shorter-lived antibody response than multiple immunizations.